Problems of quantitative assessment of the friction couple contact area - V.O. Belavin; Yu.V. Brylkin; S.V. Zaletaev; A.L. Kusov; V.V. Pavlikov; A.A. Potapov; V.A. Tsarkova (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
The results of our research of the surface of steel disks before and after friction are presented. Problems of the friction couple contact area estimation were under consideration. The results of searching a universal criterion of the friction couple contact area quantitative estimation are discussed. Using optical and scanning tunneling microscopy allows studying the surface profile at the micro- and nanoscales. An approach for determination of the contact area between bodies is proposed on the basis of the fractals theory. Such an approach allows to describe the heat transfer between bodies (conductive at contacts and radiant in pores heat exchange), to define the dependence of the friction force on the applied external force. The offered technique for the quantitative estimation of the surface structure at the micro- and nanoscales by means of the fractal theory will allow improving the accuracy of the spacecrafts thermal modes calculation as well as parameters of the knots of friction in them. This, in turn, will positively affect reliability and durability of the future spacecrafts. Improvement of methods in our further work will be aimed at studying tribological properties of the robotic products under the influence of the space factors and validation of the numerical modeling of the friction and heat exchange between mobile knots using results of experiments.